OPTIMASI DAYA TETAS TELUR IKAN GURAMI (Osphronemus gouramy, Lac) DENGAN PENGONTROLAN SUHU AIR - Anny Rimalia; Yulius Kisworo (EnviroScienteae, 2019)
This study aims to determine the effect of different temperatures and stocking densities and the hatching rate of Gouramy eggs with Experimental Design of Factorial Complete Randomized Design The main treatments of temperature, including A1: Temperature 28ºC and A2: Temperature 30ºC. The main treatment of stocking density includes B1: Stocking density of 10 pcs/liters and B2: Stocking density of 20 pcs/liters. The results were obtained as follows: Different temperatures did not have a significant effect on the hatching rate of Gouramy eggs. Different stocking densities have a significant effect on the hatching rate of Gouramy eggs. The interaction of temperature and stocking density did not have a significant effect on the hatching rate of Gouramy eggs. From the results of measurements of water quality parameters obtained water temperature data 28 and 30 ° C, pH 7.3 - 8.5 and DO (dissolved oxygen) ranged from 4.68 to 5.00 ppm